Comparison of Percutaneous K-wire and T-plate Fixation in Treatment of Distal Radius Fractures - Wutphiriya-angkul, MD, Somboon (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: The most effective method for the surgical treatment of distal radius fractures has not been established. Two commonly used techniques are percutaneous K-wire and T-plate fixation. We performed a retrospective study to compare these two treatment strategies. Methods: A total of 68 patients were selected for review. Each patient was treated by one of the two methods. Data including operative time, pain scale, radiological result, disabilities of the arm shoulder and hand (DASH) score, and operative complications were collected. Results: Thirty-six patients were treated with percutaneous K-wire, and the rest (32) were treated with T-plate fixation. The percutaneous K-wire group was associated with significantly shorter operative times and length of hospital stays, and lower postoperative pain (P<0.05), but had more complications (P=0.033). There were no significant differences in DASH scores and radiological results between the two groups. Conclusion: The percutaneous K-wire technique is similar in effectiveness to the T-plate in the treatment of distal radius fractures with shorter operative times and hospital stays, and lower postoperative pain, but had more complications.